Integration of Saving Matrix-Fishbone as Monitoring of Logistics Route PT. XYZ - Budyi Siswanto; Sindy Nindia Maretha HarisTanti; Nabila Dzatil Hidayah (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Indonesia, with 2/3 of its territory being oceans, has the potential to have abundant natural resources in the form of salt. PT. XYZ is the only state-owned company that produces products salt start from process upstream until Downstream, with Wrong One product flagship is salt diet. The biggest challenge in Supply Chain Management at the company is capability compete in providing competitive prices so it is necessary to properly study the costs in the process of distribution and logistics do not charge much in the components of the Cost of Good sold . In study This discuss related determination router best with use method saving Matrix by comparing the Neasrest Insert and Nearest Neighbor algorithms , which is then carried out analysis using Fishbone Diagram in mapping the source of constraints in the distribution process and logistics that focus on 5M+1E elements. The results of this study can be determined by 4 shipping routes according to the Nearest Neighbor algorithm . Improvements to problems that arise in existing conditions can be carried out by adding tools and infrastructure to the loading process facilities, such as hand pallets, forklifts as well as the construction of a loading dock including SOPs that regulate and can be used to measure effectiveness process loading. Indonesia, with 2/3 of its territory being oceans, has the potential to have abundant natural resources in the form of salt. PT. XYZ is the only state-owned company that produces products salt start from process upstream until Downstream, with Wrong One product flagship is salt diet. The biggest challenge in Supply Chain Management at the company is capability compete in providing competitive prices so it is necessary to properly study the costs in the process of distribution and logistics do not charge much in the components of the Cost of Good sold . In study This discuss related determination router best with use method saving Matrix by comparing the Neasrest Insert and Nearest Neighbor algorithms , which is then carried out analysis using Fishbone Diagram in mapping the source of constraints in the distribution process and logistics that focus on 5M+1E elements. The results of this study can be determined by 4 shipping routes according to the Nearest Neighbor algorithm . Improvements to problems that arise in existing conditions can be carried out by adding tools and infrastructure to the loading process facilities, such as hand pallets, forklifts as well as the construction of a loading dock including SOPs that regulate and can be used to measure effectiveness process loading. Keywords : Salt, logistics, diagram fishbone, saving matrix, nearest insert, nearest neighbors.